(untitled) (Tribhuvan University Journal of Microbiology, 2018)
Objectives: The purpose of this study was to assess microbial load and Methicillin Resistant Staphylococcus aureus from surfaces of public transport vehicle. Methods: The surfaces of public transport vehicle were sampled by swabbing. A total of 56 samples from 28 different vehicles operating in Kathmandu valley were collected and processed according to the standard methodology. The isolates were identified by culture, biochemical tests and subjected to antimicrobial susceptibility testing by modified Kirby-Bauer disk diffusion method following CLSI 2013 guidelines. Methicillin resistant species of Staphylococcus were detected by the virtue of cefoxitin resistance. Results: All 56 samples from the 28 different vehicles were found to have bacterial growth with average bacterial load of 2.47±1.22 x 105 CFU/cm2. The gas vehicles were found to be the most contaminated. Out of 56 samples, 35 (25.9%) were found to be S. aureus growth positive 11 (31.4%) of them being MRSA. Conclusion: The high flow of people with different health conditions in public transport makes the exchange of microorganism more significant. High bacterial load along with MRSA indicates the threats of transmission of infection among travellers. This is of a great public health concern as the mass population of different health condition is in direct exposure and is prone to get infected.